Computers and Education E-Learning, From Theory to Practice - Fernández-Manjón, Baltasar; Sánchez-Pérez, Juan Manuel; Gómez-Pulido, Juan Antonio; Vega-Rodríguez, Miguel Angel; Bravo-Rodríguez, José (Springer Netherlands : Imprint: Springer, 2007)
This book contains a selection of contributions presenting the latest research in the field of Computers in Education and, more specifically, in E-Learning. The topics covered range from proposals regarding the newest "de facto" standards in E-Learning - such as IMS Learning Design - to the more practical aspects of the design, i.e. implementations and the actual application of educational tools in real settings. The volume reflects the diverse scenario of the application of computers in the educational field by describing previous experiences and addressing some of the present key issues such as Learning Management Systems as well as more innovative aspects such as personalized or ubiquitous learning.